Prise en compte des hydrosystèmes hérités par les parcs naturels régionaux de Lorraine et du Morvan - Emmanuel Chiffre; Denis Mathis (Territoire en Mouvement)
The natural regional park of Lorraine and Morvan must ensure the management and the development of a huge fishery and hydraulic heritage, inherited from former facilities. Built around traditional activities today abandoned, these hydrosystems rely on new features favored by the action of the two parks. They have incorporated water resources in their territorial projects centered on an important heritage stagnustre and lacustrine, while bringing together new actors for better complementarity actions. Under the concept of a rational use of these water systems under environmental and heritage preservation, these parks have built two models of management of the water resource, seeking to build long-lasting leisure and tourism activities for these territories. This global approach seeks to maintain a balance between protection, preservation of a landscape of water and its improvement by new uses for a sustainable territorial development.